Analisis Finansial Usahatani Buah Naga Super Merah (Hylocereus costaricensis) (Studi Kasus di Kelompok Tani Berkah Naga Desa Sambirejo Kecamatan Bangorejo Kabupaten Banyuwangi) - TIYAS, AYUNING; PUTRA, I GEDE SETIAWAN ADI; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Financial Analysis of Farm Management Super Red Dragon Fruit (Hylocereus costaricensis ) (Case Study at Berkah Naga Farmer’s Group in Sambirejo Village Bangorejo District Banyuwangi Regency ) Dragon fruit is one of the horticulture commodities has a good agribusiness prospect. High demand and high selling price from dragon fruit giving opportunities to the farmer in Sambirejo village who are member of Berkah Naga Farmer’s Group to farm management dragon fruit. In a farm management dragon fruit needs financial analysis for measure the success of farming. The purpose this research is to knowing the feasibility farm management dragon fruit in term of financial aspect and household income contribution. This research was conducted at Berkah Naga Farmer’s Group in Sambirejo village, Bangorejo district, Banyuwangi regency. After all of the data calculated use investment criteria that is: NPV (Rp154.738.558,00), Net B/C (1,90) bigger than one, IRR  (59,03%) bigger than discount factor, and payback period (2 years 3 month). This results showed prevailing interest rate 18% each year, farm management dragon fruit is feasible. From sensitivity analysis showing that farm management dragon fruit not sensitive to increase cost. But, farm management dragon fruit are sensitive with decrease selling price dragon fruit 50%. Keyword : financial analysis, sensitivity analysis, super red dragon fruit